تصميم نموذج لاخطي لمحرك سيرفو ذو مقاومة متغيرة ومحاكاته لتحديد مجال عمله بدقة في فضاء (سرعة، عزم عطالة، معامل احتكاك) - إياد حاتم; مجد شاهين (Tishreen University, 2018)
Direct current radio control (DC RC) servo motors are affected by nonlinear factors in its internal structure, these factors are: • The integrated gearbox's clearance, inertia torque • The lost transmitted energy across it. • The friction in DC Motor axis. • The accuracy of controller and the effect of bang-bang control method. • The dead angle that is allowed for garneted a stable work point. These factors effect on DC RC servo motor output Characteristics in case of step pulse response and nonlinearity irregular motor angular output fixed angular speed (ramp). In this research paper we designed a non-linear module taking into consideration the mentioned factors and we declare its output behavior in three cases of work (no-load, with various inertia torque load values, and with various friction factors load values).   We simulate the model in case of step impulse and various ramp values input to evaluate motor output accuracy according to required output and we conclude the acceptable Values of work areas of loads with various inertia torques, friction factors and angular speeds, for well-known using DC RC servo motor.   تصميم نموذج لاخطي لمحرك سيرفو ذو مقاومة متغيرة ومحاكاته لتحديد مجال عمله بدقة في فضاء (سرعة، عزم عطالة، معامل احتكاك) يتأثر أداء محركات السيرفو التي تعمل بالتيار المستمر ذات المقاومة المتغيرة (RC Servo Motor) بعوامل لاخطية في بنيتها الداخلية والتي هي • خلوصات أسنان علبة السرعة المدمجة وعزم عطالة مسنناتها. • وضياع نقل الطاقة عبر علبة السرعة. • الاحتكاك على محور المحرك. • دقة المتحكم المستخدم استخدامه للتحكم من النمط فصل وصل (bang-bang). • الزاوية الميتة المسموح بها لضمان عدم اضطراب المحرك. يظهر تأثير هذه العوامل على خواص خرج المحرك في حالة النبضة الواحدية (step impulse) بالإضافة لعدم خطية وعدم انتظام حركة المحرك عند سرعات زاوية معينه (Ramp). في هذا البحث قمنا بتصميم نموذج لاخطي لمحرك سيرفو ذو مقاومة متغيرة مع مراعاة العوامل المؤثرة المذكورة مع توضيح سلوكه عند عمله في ثلاث حالات (بدون حمل، مع أحمال ذات عزوم عطالة مختلفة، مع أحمال ذات معاملات احتكاك متعددة)، حيث تمت عملية محاكاة لنموذج بنمطي النبضة الواحدية وسرعات ثابتة متعددة لتقييم دقة خرج المحرك نسبة للخرج المرغوب، استنتجنا مجالات العمل المقبولة للحمولة ذات عزم العطالة ومعامل الاحتكاك وسرعات العمل، وذلك من أجل محرك سيرفو ذو بارامترات معروفة.